Synchronous evaporation and aquatic primary production in tropical river networks. (15th July 2021) - Zhong, Jun; Wallin, Marcus B.; Wang, Wanfa; Li, Si-Liang; Guo, Laodong; Dong, Kejun; Ellam, Rob M.; Liu, Cong-Qiang; Xu, Sheng
Highlights: Large amounts of water and dissolved inorganic carbon were lost in the rivers of Hainan Island. Significant evaporation and primary production co-existed in these tropical rivers. Intensive in-stream hydrological and biogeochemical processes mainly occurred in headwater segments. Abstract: Rivers play an important role in global water and carbon cycling, but there are still large uncertainties concerning evaporation and aquatic photosynthesis. Here we combined measurements of water chemistry, isotopic compositions (i.e., δ D w, δ 18 O w, δ 13 C DIC and ▵ 14 C DIC ) and geographic characteristics (i.e., river width) to elucidate in-stream hydrological and biogeochemical processes across rivers in Hainan Island, China. The results showed that dissolved inorganic carbon (DIC) in river waters was largely of modern origin, with about 95% from contemporary biogenic sources based on an isotopic mass balance of ▵ 14 C DIC . Significant evaporation and aquatic primary production co-occurred in these tropical rivers with large amounts of water and DIC being rapidly turned over in the water column, altering the water cycle and the carbon balance. High rates of evaporation and aquatic primary production were observed in the headwater segments, with narrow river width but broad available reactive surface area at the air-water interface. The asymmetric aquatic photosynthesis at different river segments caused the spatial heterogeneities of dissolved solutes. The results suggest that the available reactive area at the water-air interface is responsible for synchronous water loss and dissolved carbon evolution in flat tropical rivers. This study provides evidence that intense evaporation and aquatic photosynthesis mainly occurred in headwater segments, which has implications for understanding global carbon cycling. Graphical abstract: Image, graphical abstract